Evaluation of the Mechanical Properties of Microcapsule-Based Self-Healing Composites. (16th February 2016) - Guadagno, Liberata; Raimondo, Marialuigia; Vietri, Umberto; Naddeo, Carlo; Stojanovic, Anja; Sorrentino, Andrea; Binder, Wolfgang H.
Abstract : Self-healing materials are beginning to be considered for applications in the field of structural materials. For this reason, in addition to self-healing efficiency, also mechanical properties such as tensile and compressive properties are beginning to become more and more important for this kind of materials. In this paper, three different systems based on epoxy-resins/ethylidene-norbornene (ENB)/Hoveyda-Grubbs 1st-generation (HG1) catalyst are investigated in terms of mechanical properties and healing efficiency. The experimental results show that the mechanical properties of the self-healing systems are mainly determined by the chemical nature of the epoxy matrix. In particular, the replacement of a conventional flexibilizer (Heloxy 71) with a reactive diluent (1, 4-butanediol diglycidyl ether) allows obtaining self-healing materials with better mechanical properties and higher thermal stability. An increase in the curing temperature causes an increase in the elastic modulus and a slight reduction of the healing efficiency. These results can constitute the basis to design systems with high regenerative ability and appropriate mechanical performance.